Tingkat Kelangsungan Hidup Dan Pertumbuhan Udang Galah (Macrobrachium Rosenbergii De Man) Pada Media Bersalinitas - agus waluyo; mulyana mulyana; fauzan ali (Universitas Djuanda, 2018)
The aim of this research was to know the effect of salinity on survival rate and growth of Macrobrachium rosenbergii. The treatments are 0 ppt (control), 3 ppt, 6 ppt, 9 ppt, 12 ppt, and 15 ppt. The survival rate, length growth, weight growth, and daily growth rate have been evaluated. This research showed there were significantly different between the treatments on survival rate and weight growth (P<0.05). The highest of survival rate get from treatment with salinity 3 ppt, 6 ppt, 9 ppt and 12 ppt. The highest of weight growth get from treatment with salinity 0 ppt, 3 ppt, 6 ppt and 9 ppt. This research showed there were not significantly different between the treatments on the daily growth rate and length growth (P>0.05). Key words: Salinity, survival rate, growth, Macrobrachium rosenbergii